Evolution and evaluation of autologous mini punch grafting in vitiligo - Lahiri Koushik (Wolters Kluwer Medknow Publications, 2009)
Vitiligo is a result of disrupted epidermal melanization with an undecided etiology and incompletely understood pathogenesis. Various treatment options have resulted in various degrees of success. Various surgical modalities and transplantation techniques have evolved during the last few decades. Of them, miniature punch grafting (PG) has established its place as the easiest, fastest, and least expensive method. Various aspects of this particular procedure have been discussed here. The historical perspective, the instruments, evolution of mini grafting down the ages, and the methodology, advantages, and disadvantages have been discussed. A detailed discussion on the topic along with a review of relevant literature has been provided in this article.